Some Digital Editions and Some Remaining Challenges - Peter Boot (Janus: Estudios sobre el Siglo de Oro)
While the digital edition has made enormous progress since the advent of the web, there is also much that we still don't know how to achieve. I examine a number of editions and some things they have taught us. Then I discuss a few open questions regarding digital editions: how to involve volunteers in the creation and upkeep of the edition, how to lower the cost of creating editions and how to deal with threats to their longevity.